Storm surges and extreme storms in Sakhalin Island and South Kuril Islands - Shevchenko Georgy; Kato Ekie; Khuzeeva Marina (MATEC Web of Conferences, 2019)
Storm surges (the significant sea level rises due to a drop in surface atmospheric pressure and an increase in wind velocity during the passage of deep cyclones over the coastal areas) pose a formidable threat to the coastal settlements of Sakhalin and the South Kuril Islands. As a result of flooding of coastal areas, the impact of storm waves on the shores and coastal facilities is sharply increased. The greatest damage caused by surges on 10.11.1990 and 9.11.1995 which affected the most populated southern part of Sakhalin Island. A long-term sea level series were analyzed, recorded at 9 coastal tide gauges located on the coast of Sakhalin Island and South Kuril Islands. Estimates for the maximum heights of the storm surges and tidal level were obtained separately, as well as for the rare recurrence of the total sea level height with the probability of these individual components superposition. The maximum total height of the sea level was obtained for the Kurilsk station, where the highest storm surge was recorded. The minimum values were obtained for southwestern coast of Sakhalin Island (Kholmsk and Nevelsk stations) were tides are small. Seasonal and inter-annual variations of strong waves were analysed from the data of visual observations.